SEASONAL VARIATION OF TRYPANOSOMA SP. FROM THE FISHES OF AURANGABAD, INDIA - POKALE, S. S.; NIKAM, S. R.; SHAIKH, J. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
During the present study of the host Channa punctatus has been examined seasonally from Aurangabad. The survey covers the relative prevalence of incidence of Trypanosoma sp. During the period 2000 - 2001. 251 hosts were examined, out of which 30 were positive. The percentage of incidence was 11%. This study shows that the percentage of incidence was low during winter, relatively higher in Summer and moderate in monsoon.